தென்னிந்தியாவில் சமூக ஊடகங்கள் - Social Media in South India (Tamil) - Venkatraman, Shriram (Why We Post, 2019)
One of the first ethnographic studies to explore use of social media in the everyday lives of people in Tamil Nadu, Social Media in South India provides an understanding of this subject in a region experiencing rapid transformation. The influx of IT companies over the past decade into what was once a space dominated by agriculture has resulted in a complex juxtaposition between an evolving knowledge economy and the traditions of rural life. While certain class tensions have emerged in response to this juxtaposition, a study of social media in the region suggests that similarities have also transpired, observed most clearly in the blurring of boundaries between work and life for both the old residents and the new. Venkatraman explores the impact of social media at home, work and school, and analyses the influence of class, caste, age and gender on how, and which, social media platforms are used in different contexts. These factors, he argues, have a significant effect on social media use, suggesting that social media in South India, while seeming to induce societal change, actually remains bound by local traditions and practices.